Characterization and Properties of PP/NBR/EFB Composites with PPMAH CompatibiLizer - Khalid Mohamed Abdillahi (School of Environmental Engineering, University Malaysia Perlis, 2016)
Investigate the characterization and properties of polypropylene, Acrylonitrile Butadiene Rubber, Empty Fruit Bunch composite. Study the mechanical properties of PP/NBR/EFB composites. Investigate the effect of use Maleic graft polypropylene (PPMAH) as Compatibilizer on the properties of PP/NBR/EFB composite.